Rhegmatogenous retinal detachments associated to Stickler syndrome in a tertiary eye care center in Saudi Arabia - Alshahrani ST (Dove Medical Press, 2015)
Saeed T Alshahrani,1 Nicola G Ghazi,2 Saba Al-Rashaed2 1Ophthalmology Department, King Fahad Specialist Hospital, Dammam, 2Vitreoretinal Department, King Khaled Eye Specialist Hospital, Riyadh, Kingdom of Saudi Arabia Purpose: To investigate the clinical findings and outcomes of rhegmatogenous retinal detachment (RRD) in Stickler syndrome on affected and fellow eyes that underwent prophylactic retinopexy.Patients and methods: Chart review of 70 eyes (62 patients). Incidence of RRD, postoperative visual acuity, and risk factors were evaluated.Results: Twenty-two patients (35%) had RRD in the fellow eye, 37% of the eyes had cataract, 93% had macular detachment, 50% had proliferative vitreoretinopathy, and 41% had posterior vitreous detachment. Success rates were: 60% of patients after scleral buckling; 57.1% after pars plana vitrectomy; and 75% after combined scleral buckling and pars plana vitrectomy. Sixty-one (93.8%) of patients had successful surgery (including second surgery). Silicone oil tamponade was significantly associated with final anatomic outcome, with a protective odds ratio of 0.11 (P=0.027). Visual acuity improved in 54% of eyes and decreased in 5%. Statistically significant associations were present for eyes with final visual acuity ≥20/200, and total retinal detachment (P<0.001); preoperative cataract (P=0.023); and proliferative vitreoretinopathy (P<0.001). RRD developed in 16/44 eyes despite laser prophylaxis.Conclusion: Prophylactic retinopexy was not beneficial for Stickler syndrome patients. Success of primary surgery for RRD remains low. The primary surgery should be vitrectomy combined with scleral buckling and silicone oil tamponade. Keywords: Stickler syndrome, retinopexy, Gulf States, Saudi Arabia, ocular genetics, arthro-ophthalmopathy, collagen disorder